Strategi Penyediaan Fasilitas Ruang Publik Inklusif di Kota Lama Semarang Berdasarkan Persepsi dan Preferensi Lansia - Valian Aulia Pradana; Djoko Suwandono; Nurini Nurini (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2023)
A good public space must be friendly and accommodating to everyone, including the elderly. Elderly is a group that has limitations when they are in public spaces because of their different needs. To find out the needs of the elderly in public spaces, it is necessary to understand their perceptions and preferences for the facilities provided so that the elderly do not need to adapt. The purpose of this study is to determine the perceptions and preferences of the elderly in the provision of inclusive public spaces in Kota Lama Semarang. Analysis of the perceptions and preferences of the elderly was carried out on three aspects, namely accessibility, comfort and safety. Data collection was carried out through filling out questionnaires by 60 elderly in Kota Lama Semarang area. This study uses Likert scale as measuring tool for the perceptions and preferences of the elderly. The conclusion from the three aspects studied, the perception of the elderly in the condition of public space facilities shows that there are advantages and disadvantages. While the preferences of the elderly in the provision of public space facilities show that the elderly agree if procurement, additions, or improvements to facilities related to the three aspects studied. The strategy for providing inclusive public space facilities can follow the standards or best practices in other cities or countries, but does not leave the classic nuance which is the identity of the Kota Lama Semarang.